Impact of Pesticide Resistance on Toxicity and Tolerance of Hostplant Phytochemicals in Amyelois Transitella (Lepidoptera: Pyralidae). Issue 1 (22nd August 2016) - Bagchi, Vikram A.; Siegel, Joel P.; Demkovich, Mark R.; Zehr, Luke N.; Berenbaum, May R.
Abstract: For some polyphagous insects, adaptation to phytochemically novel plants can enhance resistance to certain pesticides, but whether pesticide resistance expands tolerance to phytochemicals has not been examined. Amyelois transitella Walker (navel orangeworm) is an important polyphagous pest of nut and fruit tree crops in California. Bifenthrin resistance, partially attributable to enhanced cytochrome P450 (P450)-mediated detoxification, has been reported in an almond-infesting population exposed to intense pesticide selection. We compared the toxicity of bifenthrin and three phytochemicals–chlorogenic acid, and the furanocoumarins xanthotoxin and bergapten–to three strains of A. transitella : pyrethroid-resistant R347 (maintained in the laboratory for ∼10 generations), fig-derived FIG (in the laboratory for ∼25 generations), and CPQ–a laboratory strain derived from almonds ∼40 years ago). Whereas both Ficus carica (fig) and Prunus dulcis (almond) contain chlorogenic acid, furanocoumarins occur only in figs. Both R347 and FIG exhibited 2-fold greater resistance to the three phytochemicals compared with CPQ; surprisingly, bifenthrin resistance was highest in FIG. Piperonyl butoxide, a P450 synergist, increased toxicity of all three phytochemicals only in CPQ, implicating alternate tolerance mechanisms in R347 and FIG. To test the ability of the strains to utilize novel hostplants directly, we compared survival on diets containing seeds of Wisteria sinensis and Prosopis pallida, two non-host Fabaceae species; survival of FIG was highest and survival of R347 was lowest. Our results suggest that, while P450-mediated pesticide resistance enhances tolerance of certain phytochemicals in this species, it is only one of multiple biochemical adaptations associated with acquiring novel hostplants.